2008
DOI: 10.1002/ar.20735
|View full text |Cite
|
Sign up to set email alerts
|

3D Computerized Model for Measuring Strain and Displacement of the Brachial Plexus Following Placement of Reverse Shoulder Prosthesis

Abstract: The aim of the present study was to develop a method for threedimensional (3D) reconstruction of the brachial plexus to study its morphology and to calculate strain and displacement in relation to changed nerve position. The brachial plexus was finely dissected and injected with contrast medium and leaden markers were implanted into the nerves at predefined places. A reverse shoulder prosthesis was inserted in a cadaveric specimen what induced positional change in the upper limb nerves. Computed tomography (CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 47 publications
2
35
0
2
Order By: Relevance
“…The fourth lumbar (L4) nerve roots were exposed bilaterally via posterior dissection (laminectomy and facetectomy) from L3 to L5. After dissection and clear visualisation of the L4 root, 0.2 cc of dye solution (2:1 human plasma: 1% Toluidine Blue Stock Solution) 34 was injected into the L4 nerve root just proximal to the dorsal root ganglion expansion. This injection was administered via a syringe (1 cc) and a 0.45 × 23 mm needle at a location just deep to the epineurium.…”
Section: Dissection and Specimensmentioning
confidence: 99%
“…The fourth lumbar (L4) nerve roots were exposed bilaterally via posterior dissection (laminectomy and facetectomy) from L3 to L5. After dissection and clear visualisation of the L4 root, 0.2 cc of dye solution (2:1 human plasma: 1% Toluidine Blue Stock Solution) 34 was injected into the L4 nerve root just proximal to the dorsal root ganglion expansion. This injection was administered via a syringe (1 cc) and a 0.45 × 23 mm needle at a location just deep to the epineurium.…”
Section: Dissection and Specimensmentioning
confidence: 99%
“…Biomechanically, the Grammont-type reverse total shoulder arthroplasty lengthens the arm by an average of 2 to 3 cm, 4) and therefore can put strain on the brachial plexus. Van Hoof et al 9) reported the degree of strain placed on elements of the brachial plexus using 3-dimensional computer modeling in the reverse total shoulder arthroplasty. Their model calculated direct prosthesis-related strains as up to 19.3% for some components of the brachial plexus.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have estimated an increase in strain between 15 and 20% on the medial and lateral roots of the median nerve with implantation of a reverse prosthesis (Van Hoof et al, 2008). As opposed to plexopathies complicating anatomic replacement, which most likely occur secondary to transient stretching during surgery, the increased tension on the brachial plexus may be more permanent with reverse arthroplasty, although a different rate of spontaneous recovery has not been reported.…”
Section: Complicationsmentioning
confidence: 96%
“…Secure fixation of the glenoid component, the height and orientation of the humeral component, and restoration of an ideal tension on the soft-tissues, and specifically the deltoid, are some of the challenges faced when a reverse shoulder arthroplasty is implanted. Some studies have analyzed the importance of the anatomy of the scapula on fixation of the glenoid component (Humprey et al, 2008;Middernacht et al, 2008), the adverse consequences of central implantation of the glenoid component on notching (Levigne et al, 2008), and the strain on the brachial plexus after implantation of a reverse prosthesis (Van Hoof et al, 2008). However, further research needs to be completed to clarify these and other aspects of the shoulder anatomy as it relates to reverse designs.…”
Section: Introductionmentioning
confidence: 97%